METHIMAZOLE-INDUCED AGRANULOCYTOSIS AND THYROID STORM TREATED WITH LITHIUM AND TOTAL THYROIDECTOMY - Cano-Laynesa, Lucille Phylicia; Young, Louisse Lynn Antoinette; Guevarra, Patricia Marie Crisostomo (Journal of the ASEAN Federation of Endocrine Societies, 2023)
CASE A 54-year-old Filipino female diagnosed case of nodular toxic goiter for 1 month on Methimazole developed palpitations, high-grade fever, and mouth sores. She presented at the emergency room with dyspnea, jaundice, diarrhea, and atrial fibrillation and managed as a thyroid storm. Her thyroid function test showed suppressed TSH with elevated FT3 and FT4, positive TRAb, and CBC revealed agranulocytosis with an absolute neutrophilic count of 60. The patient was started on colony-stimulating factor and broad-spectrum antibiotics for febrile neutropenia. Furthermore, the patient was treated with hydrocortisone, propranolol, and lithium. Though lithium carbonate is not utilized as a standard regimen in the management of thyroid storm, it is known to inhibit the release of thyroid hormone from the thyroid gland. The patient was rendered euthyroid on medical treatment using lithium prior to the contemplated total thyroidectomy given the presence of hypofunctioning nodules on thyroid scintigraphy. Postoperatively, histopathologic examination revealed multinodular colloid adenomatous goiter.